The role of temporal contrast and blue light in emmetropization. (October 2018) - Rucker, Frances; Henriksen, Mark; Yanase, Tiffany; Taylor, Christopher
Highlights: The eye is vulnerable to myopia with exposure to low contrast visual stimuli. Exposure to low temporal frequency visual stimuli increases vulnerability. As does a yellowish light source without a strong blue component. Abstract: A previous experiment showed that blue light (as a component of white light) protected against low temporal frequency dependent eye growth. This experiment investigated the role of temporal contrast. White leghorn chicks were exposed to white (with blue) or yellow (without blue) LED lighting modulated at either low (0.2 Hz) or high (10 Hz) temporal frequencies. Four cone contrast conditions were used: low (16%), medium (32%), medium–high (60%) and very-high (80%). Chicks were exposed to the lighting condition for 3 days (mean 680 lux). Exposure to high temporal frequencies, with very high temporal contrast, reduced eye growth, regardless of spectral content. However, at low temporal frequencies, eye growth was dependent on the illuminant. At lower temporal contrast levels, growth increased regardless of temporal or spectral characteristics. To conclude, very high temporal contrast, white light, provides a "stop" signal for eye growth that overrides temporal cues for growth that manifest in yellow light.